Evaluation and application of a mixed‐mode chromatographic stationary phase in two‐dimensional liquid chromatography for the separation of traditional Chinese medicine. Issue 12 (6th June 2016) - Wei, Zhishen; Fu, Qing; Cai, Jianfeng; Huan, Liyun; Zhao, Jianchao; Shi, Hui; Jin, Yu; Liang, Xinmiao
Abstract : In this study, two mixed‐mode chromatography stationary phases (C8SAX and C8SCX) were evaluated and used to establish a two‐dimensional liquid chromatography system for the separation of traditional Chinese medicine. The chromatographic properties of the mixed‐mode columns were systematically evaluated by comparing with other three columns of C8, strong anion exchanger, and strong cation exchanger. The result showed that C8SAX and C8SCX had a mixed‐mode retention mechanism including electrostatic interaction and hydrophobic interaction. Especially, they were suitable for separating acidic and/or basic compounds and their separation selectivities could be easily adjusted by changing pH value. Then, several off‐line 2D‐LC systems based on the C8SAX in the first dimension and C8SAX, C8SCX, or C8 columns in the second dimension were developed to analyze a traditional Chinese medicine— Uncaria rhynchophylla . The two‐dimensional liquid chromatography system of C8SAX (pH 3.0) × C8SAX (pH 6.0) exhibited the most effective peak distribution. Finally, fractions of U. rhynchophylla prepared from the first dimension were successfully separated on the C8SAX column with a gradient pH. Thus, the mixed‐mode stationary phase could provide a platform to separate the traditional Chinese medicine in practical applications.